PERBEDAAN KEMAMPUAN PASTA GIGI DESENSITISASI KOMERSIAL DENGAN BAHAN AKTIF HIDROKSIAPATIT DAN NOVAMIN DALAM PENUTUPAN TUBULUS DENTIN DENGAN SCANNING ELECTRON MICROSCOPE - Hardita Bicevani Mulya; Andina Rizkia Putri Kusuma; Aning susilowati (ODONTO : Dental Journal, 2016)
Background: The use of commercial desensitization toothpaste is one of the way to treat dentine hypersensitivity. Desensitization tooth paste contains an active ingredient which is able to occlude the dentinal tubules to minimize the movement of fluid in the dentinal tubules which lead to dentin hypersensitivity. Desensitization toothpaste containing various kind of active ingredients for occluding the dentinal tubules. The purpose of this research was to determine the differences of desensitization tootpaste ability (Pepsodent Sensitive Expert® and Sensodyne Repair and Protect®)inoccluding dentinal tubules with different active ingredient (hydroxyapatite and Novamin).Method: The research is experimental laboratories with post test group design. The sample used was 8 dentin disc with 8 mm length and 3 mm width, the sample was divided into two groups thattreated with Pepsodent Sensitive Expert® desensitization toothpaste and the group treated with Sensodyne Repair and Protect® desensitization toothpaste. A non-parametric data analysis was carried out by MannWhitney(<0.05). Result:The result showed that there were no significant differences in the percentage of dentinal tubulesin both treatment groups.Conclusion:The conclusion of this research is both of Pepsodent Sensitive Expert® and Sensodyne Repair and Protect® desensitization tootpaste have the same ability in occluding the dentinal tubules.